Driver characteristics associated with child safety seat usage in Malaysia : a cross-sectional study. - K.C. Mani@Subramaniam, Kulanthayan; Ahmad Razak,; Schenk, Ellen (Elsevier Limited, 2010)
Background: The rapidly motorizing environment in Malaysia has made child occupant safety a current public health concern. The usage of child safety seats (CSS) is a widely regarded intervention to enhance child occupant safety, yet no study has been conducted on CSS in Malaysia. This study aims to determine the CSS usage rates in Malaysia and to assess driver characteristics that are associated with CSS usage.